Answer:
f(-2) = 4
f(0) = 6
f(5) = 11
Step-by-step explanation:
You just need to plug in the different values of x into the equation
f(x)=x+6
When x = -2, then f(-2) = -2 + 6 = 4
When x = 0, then f(0) = 0 + 6 = 6
When x = 5, then f(5) = 5 + 6 = 11
N = 3 i = 2
2 x 2 = 4
3 x 3 = 9
4 + 9 = 13
13 = area
Answer:
5-6i
Step-by-step explanation:
The complex conjugate root theorem states that if (a+bi) is a root, then (a-bi) must also be a root and vice versa.
We know that (5+6i) is a root.
Then by the above theorem, (5-6i) must also be a root.
Hence, our solution is (5-6i).
Let's translate each sentence into "Math".
Pineapple = p
Orange = x
is means equal
Pineapple is 7 times as heavy as an orange: p = 7x
Pineapple weighs 870 grams more than orange. p = 870 + x
Substitute p = 7x into the second equation:
7x = 870 + x
Subtract x from both sides
6x = 870
divide by 6
x = 145
The orange weighs 145 grams.
The pineapple weights 7 times the orange = 7(145) = 1015 grams.
B*H = area of rectangle so do 100/5 to get base so Base=20m